The Abundance of Epibenthic Dinoflagellates Toxic (Gambierdiscus sp., Prorocentrum sp. and Ostreopsis sp) in Seaweed Padina sp in Coastal Waters of Sungai Nipah Village Pesisir Selatan District West Sumatra Province - Sentosa Yeremia; Thamrin '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The species existence of dinoflagellates , i.e. Gambierdiscus sp., Prorocentrum sp. and Ostreopsis sp in the waters can cause disease, poisoning and blooming. This will cause disruption of aquatic ecosystems that cover the water surface and light penetration into the body of water will be hampered. Research to determine the abundance of toxic dinoflagellate epibenthic on seaweed Padina sp. in Sungai Nipah waters was conducted in August 2015. Sampling of epibenthic dinoflagellates attached to Padina sp was performed in three stations and each station consists of three sampling points.The results showed that the highest abundance epibentic toxic of dinoflagellates in the coastal waters of Sungai Nipah found at station 3 (803.28 cells / g). The highest abundance from all stations was a genus of Prorocentrum sp., with the total number of 947.74 cells/g, genus Gambierdiscus sp. had the smallest abundance at each respective station with a total of 41 cells/g while Ostreopsis sp has a evenly abundance in almost every station with a total abundance 562.93 cells/g.Keywords: Abundance, Epibenthic, Dinoflagellates, Toxic, Padina sp., Sungai Nipah Waters